2020
DOI: 10.5114/fmpcr.2020.92504
|View full text |Cite
|
Sign up to set email alerts
|

The effect of counselling on the sexual satisfaction of women with hypoactive sexual desire referring to Hamadan health centres, 2017

Abstract: Background. Sexual dysfunctions are among the factors affecting marital satisfaction. Objectives. The aim of this study was to investigate the effect of counselling on the sexual satisfaction of women with impaired sexual dysfunction referred to Hamadan health centres. Material and methods. This clinical randomised trial was conducted on 120 low-libido subjects referring to comprehensive health centres in Hamadan city. They were randomly divided into two groups of 60 women. Data collection tools included demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In a randomized trial conducted among women in Hamadan Heath Centre, counselling was found to be successful in improving libido and sexual satisfaction. 14 Furthermore, sexual counselling improves sexual intimacy and sexual satisfaction among breastfeeding women. 15 Among women with sexual dysfunction, 16 recommend the implementation of counselling in increasing levels of sexual satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…In a randomized trial conducted among women in Hamadan Heath Centre, counselling was found to be successful in improving libido and sexual satisfaction. 14 Furthermore, sexual counselling improves sexual intimacy and sexual satisfaction among breastfeeding women. 15 Among women with sexual dysfunction, 16 recommend the implementation of counselling in increasing levels of sexual satisfaction.…”
Section: Introductionmentioning
confidence: 99%